Incumbent's advantage through exploiting complementary assets via interfirm cooperation - Rothaermel, Frank T. (Strategic Management Journal, 2001)
Abstract I examine interfirm cooperation between incumbents and new entrants as a mechanism for incumbents to adapt to radical technological change through exploitation of complementary assets. The research setting is the biopharmaceutical industry, where I analyze 889 strategic alliances between 32 large pharmaceutical firms and providers of the new biotechnology. I find that incumbents that focus their network strategy on exploiting complementary assets outperform incumbents that focus on exploring the new technology. However, there are limits to this strategy due to diminishing marginal returns to alliance intensity. I am also able to show that an incumbent's new product development is positively associated with its performance. Copyright © 2001 John Wiley & Sons, Ltd.